Legal Advocacy in Indonesia: Reconstruction of the Legal Aid Model for Persons with Disabilities in the Regions - Burhanuddin Burhanuddin; Andi Bau Mallarangeng; Maskawati Maskawati (International Journal of Law, Crime and Justice, 2026)
The implementation of legal aid in Indonesia, although it has many obstacles in its implementation, normatively has a fairly strong foundation. This study examines the implementation of legal aid for persons with disabilities by focusing on the role of local governments through strategic policies in the form of regional regulations or other regulations. Based on the obstacles in its implementation, this study aims to offer a reconstruction of the legal aid model for people with disabilities in the regions. By using a normative approach to legislation, in this case the Legal Aid Law and the Law on Persons with Disabilities, this study found that access to justice for persons with disabilities can be carried out through legal aid in the regions as a form of equal rights before the law as affirmed in the 1945 Constitution of the Republic of Indonesia. In addition, this study also found that with the budgeting authority in the APBD, according to Article 19 of the Legal Aid Law, the legal aid model for persons with disabilities can be reconstructed by strengthening additional services in the form of personal assessments and translators included in legal aid procedures so that people with disabilities who face the law are more assured and assured in accessing justice.